Physical performance during water-polo matches: The effect of the players` competitive level - Botonis, P. G.; Toubekis, A. G.; Platanou, T. I. (Journal of Human Kinetics, 2016)
The purpose of the study was to compare playing intensity and performance changes within a water-polo match in players of different competitive levels. High-level (n = 7) and lower-level (n = 7) players performed a progressively increasing speed test of 5 x 200 m swimming and speed corresponding to lactate concentration of 4.0, 5.0 and 10.0 mmol•l-1 was calculated. Repeated sprint ability (8 x 20 m) was tested at pre-, the middle and post-match and a 400 m swimming test was completed at pre and post in five water-polo matches. A t-test and a two-way ANOVA were used for statistical analysis. High-level compared to lower-level players presented higher speed corresponding to lactate concentration of 4.0 and 5.0 mmol•l-1 (p < 0.05). Regardless of the sports level, the mean heart rate was reduced towards the end of the match. High-level players completed a shorter amount of match time with the heart rate lower than 85% of the peak heart rate (p < 0.05). However, when the speed corresponding to lactate concentration of 4.0 mmol•l-1 was used as a covariate, no differences were observed in the heart rate between groups. Both groups decreased repeated sprint and 400 m performance at post- compared to pre-match by 7 ± 3% and 7 ± 4%, respectively. High-level compared to lower-level players showed better performance in repeated sprints at the middle (p < 0.01) and in pre-, post-match 400 m tests (p < 0.01). It was concluded that high-level compared to lower-level players completed the match at a higher playing intensity and presented a lower performance decrement across the match as a result of their higher aerobic endurance.